2007
DOI: 10.1093/nar/gkm654
|View full text |Cite
|
Sign up to set email alerts
|

Sequence specific detection of DNA using nicking endonuclease signal amplification (NESA)

Abstract: We have developed a new method for identifying specific single- or double-stranded DNA sequences called nicking endonuclease signal amplification (NESA). A probe and target DNA anneal to create a restriction site that is recognized by a strand-specific endonuclease that cleaves the probe into two pieces leaving the target DNA intact. The target DNA can then act as a template for fresh probe and the process of hybridization, cleavage and dissociation repeats. Laser-induced fluorescence coupled with capillary el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 23 publications
0
61
0
Order By: Relevance
“…However, these methods are based on template replication, which increase the risk of cross-contamination from amplicons, so false-positive results frequently occur (Zou et al, 2011). To date, there have been several strategies based on signal amplification to selectively detect nucleic acids, including branched DNA (bDNA; Collins et al, 1997), invasive signal amplification, nicking endonuclease signal amplification (NESA; Kiesling et al, 2007), and hybridization chain reaction (HCR; Dirks and Pierce, 2004). Initial work by Dirks and Pierce has demonstrated a hybridization chain reaction, in which hairpins with overlapping partial complementarities were used to construct a reaction cascade that resulted in the formation of double-stranded DNA polymers up to thousands of base pairs long.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods are based on template replication, which increase the risk of cross-contamination from amplicons, so false-positive results frequently occur (Zou et al, 2011). To date, there have been several strategies based on signal amplification to selectively detect nucleic acids, including branched DNA (bDNA; Collins et al, 1997), invasive signal amplification, nicking endonuclease signal amplification (NESA; Kiesling et al, 2007), and hybridization chain reaction (HCR; Dirks and Pierce, 2004). Initial work by Dirks and Pierce has demonstrated a hybridization chain reaction, in which hairpins with overlapping partial complementarities were used to construct a reaction cascade that resulted in the formation of double-stranded DNA polymers up to thousands of base pairs long.…”
Section: Introductionmentioning
confidence: 99%
“…By mutating residues in the DNA-binding and cleavage domains, FokI monomer was shown to bind to the top strand of the target sequence and cleave the bottom strand and on dimerization top strand was cleaved (Sanders et al 2009). NEases have been used to label dsDNA by nick translation for the detection of specific DNA sequences (Kiesling et al 2007;Kuhn and Frank-Kamenetskii 2008). Coupled with high-resolution imaging and DNA stretching, BbvCI sites have been mapped onto λ DNA with high speed and accuracy ).…”
Section: Directed Evolutionmentioning
confidence: 99%
“…Specificity was an essential parameter of various analytical means. Previous studies have demonstrated that nicking endonucleases had a high specificity in distinguishing the target from other sequences [11,15]. In this study, the selectivity of the strategy was also investigated by using MNPs/linker DNA/CdS to hybridize with target DNA sequences, one-base mismatched DNA sequences and noncomplementary DNA sequences.…”
Section: Analytical Performancementioning
confidence: 99%
“…Since the report by Kiesling in 2007, the nicking endonuclease was employed for identification of specific DNA and to be used for signal amplification [11][12][13]. When a perfectly matched DNA hybridizes the linker DNA, a full recognition site will form for the nicking endonuclease, and the nicking endonuclease cleaves the linker DNA and releases the target to recycle [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%